Perancangan Miniatur Pintu Air Otomatis Berbasis Sensor Water Level dan Arduino Uno pada Sistem Irigasi Persawahan - Muhaimin Muhaimin; Bengawan Alfaresi; Feby Ardianto (Jurnal Serambi Engineering, 2021)
The arrangement of the floodgates for rice irrigation canals is currently still using the manual method. This is very burdensome for farmers because it requires time and energy. Therefore, we need a sluice in the irrigation canal that can be done automatically. The purpose of this research is to design a miniature sluice system that can automate the sluice gate in opening and closing the sluice gate based on the water level limit of the channel. The method used in this study is the use of Arduino Uno as data storage, a servo motor that functions as a floodgate controller, a water level sensor to open the floodgate and an ultrasonic sensor that functions to determine the water level. The results of the tool testing in the research of the miniature automatic sluice gate that has been designed, namely the automatic sluice gate will open when the water sensor at the top is exposed to water. The ultrasonic sensor will measure the distance between the sensor and the water surface to make a decision to close the floodgate. If the sensor distance with the water surface is still 14 m, then the floodgate will open 1800, if the sensor distance with the water surface is 4 cm and 14 cm, then the floodgate will open 900 and if the distance between the sensor and the water surface is 4 cm, then the floodgate will be closed.